2013
DOI: 10.1016/j.pan.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic ductal adenocarcinomas with multiple large cystic structures: A clinicopathologic and immunohistochemical study of seven cases

Abstract: Background/Objectives: Pancreatic ductal adenocarcinoma (PDA) with cystic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…This finding is similar to that in a previous report of a large series of ACP cases, which demonstrated that cyst formation occurred in nine of 35 ACP cases (26%)[ 5 ]. On the other hand, PDAC with cystic features has been reported to account for 7%-11% of all PDAC cases[ 14 , 15 ]. Kosmahl et al[ 16 ] reported that 38 of 483 (8%) cases of PDAC and its variants, including adenosquamous carcinomas and ACPs, had cystic features.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to that in a previous report of a large series of ACP cases, which demonstrated that cyst formation occurred in nine of 35 ACP cases (26%)[ 5 ]. On the other hand, PDAC with cystic features has been reported to account for 7%-11% of all PDAC cases[ 14 , 15 ]. Kosmahl et al[ 16 ] reported that 38 of 483 (8%) cases of PDAC and its variants, including adenosquamous carcinomas and ACPs, had cystic features.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 5 th edition of the World health organization (WHO) Classification of Digestive System Tumors, large duct type PDAC qualifies as a growth pattern and not as a special type of PDAC (such as adenosquamous, micropapillary or anaplastic/sarcomatoid undifferentiated carcinoma, for instance). With over two decades of research concerning this pattern of PDAC, pathologic diagnostic criteria were specified and arguments in favor to categorize the large duct pattern of PDAC as a subtype of PDAC accumulated [3,9,[11][12][13][14][15]. Irregular shaped, expanded ducts with a diameter of more than 0.5mm in the majority of the histological tumor sections (>50%), corresponding to macroscopic impression of microcysts and exclusion of mimickers set pathologists for the right diagnosis [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic ductal carcinoma, retention cysts may occur secondary to intraluminal obstruction of the pancreatic ducts. Nitta et al [ 1 ] described a series of cystic pancreatic ductal adenocarcinomas that had distinctive morphologic and immunohistochemical features. In that report, the maximal cyst diameter was 2.0 cm or more in all patients (range, 2.0–5.0 cm; mean, 3.7 cm).…”
Section: Discussionmentioning
confidence: 99%
“…In that report, the maximal cyst diameter was 2.0 cm or more in all patients (range, 2.0–5.0 cm; mean, 3.7 cm). The average tumor size including the multiple large cystic structures was 6.0 cm (range, 4.0–8.0 cm) [ 1 ]. Cystic tumors of the pancreas occur with less frequency than solid lesions, and are often detected incidentally, as many of these lesions are small and asymptomatic [ 2 ].…”
Section: Discussionmentioning
confidence: 99%